Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. BVI - Shafa Arya Akhdania; Rani Kurniasari (Global Leadership Organizational Research in Management, 2024)
Humans are an important asset in a company or organization, without someone's vision it is impossible for a company or organization to develop its vision and mission. Quality employees will play an important role in supporting the development and movement of the organization and play an important role in the organization's efforts to achieve its goals and mission. In the workplace, employee performance is very important for the success of the organization. Factors such as motivation and work environment play a very important role. Many studies have been conducted to examine the influence of work motivation and work environment on employee performance. This research aims to determine whether there is an influence of motivation and work environment on employee performance at PT. BVI Visitor Handling section either partially or simultaneously. The type of research used in this thesis is quantitative research. The research sample consisted of 39 employees using saturated sampling techniques. The data collection methods used were observation, questionnaires and literature study. The analysis used was data quality testing (validity test and reliability test), classical assumption test, hypothesis testing (T test and F test), and coefficient of determination test with the help of the SPSS version 26 application. Based on the results obtained, motivation and work environment significantly affects employee performance both partially and simultaneously.